Disciplining Gender in Environmental Organizations: The Texts and Practices of Gender Mainstreaming - Arora-jonsson, S.; Sijapati Basnett, Bimbika (Wiley, 2018)
Gender experts are being recruited and gender routinized in the everyday work of international environmental organizations today. To what extent do these changes open up spaces for reorienting sustainability debates in terms of normative commitments to promoting gender equality and justice? We explore this question by studying how gender is done in one such organization meant to work towards sustainability. We examine how work with gender is organized — the experts employed and their possibilities to influence events as well as how gender is addressed in the texts produced in the course of organizational work. We find that while abstractions for a global audience may distance debates on sustainability from people on the ground, contrary to current thinking, the depoliticized and disciplined narrative on gender can also open up a space for counter discourses on gender by providing a platform from which to destabilize dominant debates on sustainability. We suggest that a close analysis of the shaping of global and official discourses on sustainability can provide insights into how we may interrupt discourses that re/produce inequalities.